IT-Tutor: an architecture for web-based content sequencing system - Katuk, Norliza; Zakaria, Nur Haryani; Abd Wahab, Alawiyah; Ghazali, Osman (American Scientific Publishers, 2017)
This paper proposes the architecture and components of a web-based content sequencing system known IT-Tutor. It organizes an appropriate sequence of learning content based on individual students’ prior knowledge. The dynamic and flexible organization of learning content is meant to achieve adaptive computer-based learning. IT-Tutor was evaluated in two usability studies; an expert-review, and a user-test. In the first study, five experts in a usability test and instructional design evaluated the system. IT-Tutor has also been evaluated by twelve students in the second study. The usability tests revealed that IT-Tutor is a usable computer-based learning tool that can be used to support classroom teaching or employed in an independent online learning environment.